16. EFFECTIVENESS OF ELECTROACUPUNCTURE COMBINED WITH ULTRASOUND THERAPY IN IMPROVING SHOULDER JOINT FUNCTION ON PATIENTS WITH PERIARTHRITIS HUMEROSCAPULARIS (Vietnam Journal of Community Medicine, 2025)
Objectives: To evaluate the effectiveness of electroacupuncture combined with ultrasound therapy in improving shoulder joint function on patients with periarthritis humeroscapularis at National Hospital of Traditional Medicine.Method: Clinical intervention study, comparing before - after of treatment on 50 patients with periarthritis humeroscapularis, who were treated with electro-acupuncture and ultrasound therapy.Results: After 20 days of treatment, assessment based on the classification of shoulder joint range of motion according to McGill - McRomi showed a good improvement in the range of motion of the shoulder joint (abduction, internal rotation, external rotation), the difference was statistically significant with p < 0.05. Shoulder joint mobility according to Constant C.R and Murley A.H.G improved from 13.81 ± 1.94 points to 23.37 ± 2.29 points, the difference was statistically significant with p < 0.05. The difficulty SPADI score decreased from 49.36 ± 8.93 points before treatment to 13.71 ± 5.24 points after 20 days of treatment, the decreased point was 35.65 ± 6.82 points (p < 0.05). The total SPADI score decreased from 51.22 ± 8.47 points before treatment to 16.75 ± 6.39 points, a decrease of 34.47 ± 7.29 points (p < 0.05).Conclusion: Electro-acupuncture combined with ultrasound therapy is effective in treating periarthritis humeroscapularis.
Keywords: Periarthritis humeroscapularis; electro-acupuncture; ultrasound therapy.